MY ERROR IS RICH: ERREUR, HUMOUR ET ANGLAIS DES AFFAIRES / MY ERROR IS RICH: ERROR, HUMOUR AND BUSINESS ENGLISH / GREŞELILE SUNT MULTE: GREŞEALĂ, UMOR ŞI ENGLEZA DE AFACERI - Pauline Tee Anderson (Studii si Cercetari Filologice: Seria Limbi Straine Aplicate, 2017)
This article aims to explore the relationship between error and humour as they appear in a corpus of British cartoons depicting the world of work and business. This analysis reveals not only the strategies used by the cartoonists concerned, but also the fact that the theme of error is extremely rich, for example because it can be linked to questions of British mentality and culture. The potential role of these documents as teaching tools in a Business English course in Applied Languages will also be examined